Metabolic Complications of Diabetics Admitted in Emergency at the Souro-Sanou University Hospital Center, Bobo-Dioulasso (CHUSS) - ILBOUDO, Alassane; MBAYE, Salissou Seck Mbaye; Samandoulougou, Rene Severin Delwende; Zoungrana, Thibaut Joseph; Zampaligre, Idrissa; Drabo, Lakinapin Aboubacar; Ouédraogo, S Macaire (International Journal of Nutrition, 2022)
The diabetic is most of the time admitted in emergency for acute complications. An inventory of these complications will guide promotional programs aimed at preventing the occurrence of these complications. This study was conducted with the aim of identifying acute complications and decompensation factors in diabetics admitted in emergency to the Souro Sanou University Hospital Center (CHUSS).It was an observational study, of descriptive transversal type, with prospective collection for 4 months. It concerned diabetics admitted to the medical and surgical emergency departments of the CHUSS. A total of 90 diabetics were included in the study. The average age was 58.81 ± 14.7 years. Type 2 diabetes accounted for 85.6% of cases. The diagnosis of diabetes was known in 74.4% of cases. The reasons for consultation were dominated by impaired conscientiousness and fever, 54.4% and 50% respectively. Metabolic complications were found in 44.4% of patients. They were dominated by hypoglycemia, which accounted for 55.3% of cases. Dietary error was the main decompensation factor in cases of hypoglycemia and was reported in 71.4% of cases. Metabolic complications are common in diabetics admitted in emergency at the CHUSS. Decompensation factors are mostly preventable.
Keywords: Diabetes; metabolic complications; Burkina Faso.